Kreativitas Mahasiswa dalam Turnamen Game Online Mobile Legends: Bang Bang pada Ormawa UNS E-sports - Tatiana Pramudya Regita (Universitas Sebelas Maret (UNS), 2025)
The rapid development of E-sports in Indonesia is marked by the increasing number of tournaments and E-sports communities. This study aims to examine student creativity in Mobile legends: Bang Bang (MLBB) Online game tournaments within the UNS E-sports Organization and to understand the factors driving student participation in these competitions. This research employs a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation involving students actively participating in the UNS E-sports Organization. This study applies David McClelland’s Need for Achievement theory and Max Weber’s Social Action theory to explore how achievement motivation and social interaction shape student creativity.The results show that students join the UNS E-sports Organization due to their interest in E-sports, skill development, and the motivation to compete and network. Participation in MLBB tournaments is driven by the desire to test abilities, achieve success, and gain competitive experience. Student creativity in tournaments is reflected in four main aspects: fluency (idea generation and problem-solving), flexibility (adaptability in strategy), elaboration (idea development and refinement), and originality (unique and innovative approaches). These creative aspects are evident in strategic game planning, adaptation to match dynamics, and effective teamwork management. The outcomes of this creativity include achievements, real-life skill development, and increased self-confidence. This study concludes that MLBB Online game tournaments are not merely competitive arenas but also serve as platforms for students to actualize and enhance their creativity.